Marketing Strategy for Domestic and International Tour Packages at PT. Yuk Kita Tour - Siregar, Ahmad Jailani; Ginting, Paham; Harahap, R.Hamdani (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research discusses Tourism, one of the largest industries in the world and is a sector that many countries rely on. This study aims to find out the marketing strategy of tour packages in PT. Yuk Kita Tour on Domestic and International Tour Packages. This research method was carried out to consumers of PT. Yuk Kita Tour, The reason for choosing this location is because PT. Yuk Kita Tour is a travel agency that is different from other travel agencies. The types and sources of data in this study use qualitative data types, such as: the results of descriptive interviews, the potential attraction of tourists of PT. Yuk Kita Tour and two data sources, namely primary data sources and secondary data sources. In collecting data using three techniques, namely: observation where this research is carried out by direct observation of PT. Yuk Kita Tour. To determine the informants using the purposive sampling technique, the researcher determines in advance who is the sample, and mentions the status of each according to the researcher's wishes and objectives. Research Results of PT. Yuk Kita Tour Implement the SO strategy by increasing sales promotion to the target market, increasing cooperation with hotels and travel agents and maintaining diversity and innovation in product and service quality.